2014
DOI: 10.1002/mame.201400286
|View full text |Cite
|
Sign up to set email alerts
|

Photocontrol of Mechanical Properties of Pulp Fibers and Fiber‐to‐Fiber Bonds via Self‐Assembled Polysaccharide Derivatives

Abstract: Photoresponsive pulp fibers are prepared by self‐assembly of photoactive cationic cellulose derivatives with pulp fibers in aqueous environment. Photoactive groups of the derivatives undergo 2π + 2π cycloaddition reaction under UV‐light irradiation. Fast photocrosslinking leads to the formation of the covalent bonds between the photoactive groups on the fiber surfaces. This results in drastic enhancement of the mechanical properties of the fiber network. Tensile strength and Z‐directional tensile strength incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…This testing revealed that there was an increase in the unidirectional stiffness of fibers by 60% and in the strength of the fiber network from 81 to 84%. 44 Thus, the mechanical properties of both individual fibers and fiber networks can be engineering to improve the performance in smart packaging, composites, membranes, and tissue paper.…”
Section: Photocontrolled Formation Of Fiber-to-fiber Bonds Using Polymentioning
confidence: 99%
See 1 more Smart Citation
“…This testing revealed that there was an increase in the unidirectional stiffness of fibers by 60% and in the strength of the fiber network from 81 to 84%. 44 Thus, the mechanical properties of both individual fibers and fiber networks can be engineering to improve the performance in smart packaging, composites, membranes, and tissue paper.…”
Section: Photocontrolled Formation Of Fiber-to-fiber Bonds Using Polymentioning
confidence: 99%
“…(b) Visualization of the 2π + 2π cycloaddition reaction creating covalent bonds between pulp fibers and along the fibrils of the fiber. Reprinted from ref ( 44 ) with permission from John Wiley and Sons.…”
Section: Photocontrolled Formation Of Fiber-to-fiber Bonds Using Polymentioning
confidence: 99%
“…This property led such compound to potential application as solar cell materials. Grigoray et al (2015) used the same synthesis approach to produce coumarin-containing cellulose polyelectrolytes, which were used to decorate pulp fibers to prepare light-responsive pulp fibers/fibrous materials with light-controllable mechanical properties. In addition, fluorescent CNCs with carbazole and coumarin functionalities were synthesized via a one-step esterification reaction using carbazole-9-yl-acetic acid and coumarin-3-carboxylic acid respectively (Sirbu et al 2016).…”
Section: Esterified Cellulose Containing Aliphatic Moietiesmentioning
confidence: 99%
“…20 In previous works, the modification of cellulose fibers using multifunctional polysaccharide derivatives has been studied. 15,21,22 This innovative approach provides an easy way to introduce functional groups on bleached kraft wood pulp fibers (BKPP) in aqueous media, at room temperature. The method is simple, reproducible, and allows fiber functionalization without losing the excellent mechanical properties of the original fibers.…”
Section: ■ Introductionmentioning
confidence: 99%